2022
DOI: 10.1039/d1nj05938f
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of CO2 hydrogenation over a Zr1–Cu single-atom catalyst

Abstract: The effects of Zr single atom modification on the hydrogenation mechanism of CO2 to methanol on Cu (111) surface were investigated by density functional theory (DFT).  In the HCOO pathway, 11...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Moreover, some results of DFT calculations [71,83,84] and kinetic study [83] also confirm the mechanism via CO*. Thus, researchers also studied the co-existence of the two mechanisms.…”
Section: Reaction Mechanismmentioning
confidence: 75%
“…Moreover, some results of DFT calculations [71,83,84] and kinetic study [83] also confirm the mechanism via CO*. Thus, researchers also studied the co-existence of the two mechanisms.…”
Section: Reaction Mechanismmentioning
confidence: 75%
“…In addition, the H atoms spilled over to the support surface at the metal-support interface region, participated in the formation of the carbonaceous intermediate species, and were finally converted to HCOO*, CH 2 O*, CH 3 O*, and CH 3 OH. Liu et al [127] systematically explored three possible paths of CO 2 hydrogenation to methanol over a single-atom Zr-doped Cu-based catalyst from the kinetic and thermodynamic aspects of each elementary reaction by the DFT method (Figure 9). The results showed that methanol was produced by the HCOO pathway, which involved the intermediates of bi-HCOO*, HCOOH*, H 2 COO*, H 2 COOH*, H 2 CO*, and H 3 CO*.…”
Section: The Hcoo Mechanism and R-hcoo Mechanismmentioning
confidence: 99%
“…Elementary reactions, activation energies, and reaction energy of CO 2 hydrogenation to methanol over the Zr/Cu (111) catalyst168 …”
mentioning
confidence: 99%